1
$\begingroup$

I have to show that the discrete Heisenberg group H (with $a,b,c \in \mathbb{Z}$) has the presentation $H=\langle x,y\mid [[x,y],x]=[[x,y],y]=1 \rangle$.

I figured we write $H$ as a group of triples $H=\{(a,b,c) \mid a, b, c \in \mathbb{Z}\}$ with group operation defined as $(a,b,c)(a',b',c')=(a+a',b+b',ab'+c+c')$, but that is as far as I can get.

$\endgroup$
  • $\begingroup$ I don't want a full answer but I'd appreciate some hints. $\endgroup$ – W.Scott May 8 '17 at 21:37
  • $\begingroup$ First show that $x \mapsto a$, $y \mapsto b$ extends to a surjective homomorphism $G \to H$, where $G$ is the group defined by the presentation. Then show that every element of $G$ can be written in the form $x^iy^j[x,y]^k$ for some $i,j,k \in {\mathbb Z}$, and deduce that your map is injective and hence an isomorphism. $\endgroup$ – Derek Holt May 9 '17 at 8:08
  • $\begingroup$ I'm stuck in the step "show that every element of $G$ can be written as $x^{i} y^{j} [x,y]^{k}$. Specifically, I have shown $yx$ can be written in this form with $i=1, j=1, k=-1$. But what about $y^{-1} x^{-1}, y^{-1} x, yx{^-1}$ etc.? $\endgroup$ – W.Scott May 9 '17 at 10:42
  • 1
    $\begingroup$ You haven't saidf what definition of $[x,y]$ you are using. But $y^{-1}x^{-1} = x^{-1}y^{-1}(yxy^{-1}x^{-1})$ and $yxy^{-1}x^{-1} = [y,x] = [x,y]^{-1}$. $\endgroup$ – Derek Holt May 9 '17 at 10:51
  • $\begingroup$ Hmm... another approach if somebody wants to expand it into a full answer: the subgroup $\{ (a,b,c) \in H | a = 0 \}$ is split normal, and isomorphic to $\mathbb{Z}^2$; and the quotient is isomorphic to $\mathbb{Z}$. So, $H$ is a semidirect product of $\mathbb{Z}^2$ and $\mathbb{Z}$, and I think the induced map $\mathbb{Z} \to \mathrm{Aut}(\mathbb{Z}^2)$ sends $1$ to the shear $\begin{bmatrix} 1 & 1 \\ 0 & 1 \end{bmatrix}$. So, by math.stackexchange.com/questions/160870/… , since a presentation of $\mathbb{Z}^2$ is... $\endgroup$ – Daniel Schepler May 17 '17 at 20:54
2
$\begingroup$

Let $H = \{ (a, b, c) | a, b, c \in \mathbb{Z} \}$ and $H' = \langle x, y | [[x,y], x] = [[x,y], y] = 1 \rangle$. Then we can define a group homomorphism $\phi : H' \to H$ such that $\phi(x) = (1, 0, 0)$ and $\phi(y) = (0, 1, 0)$ (since the images of $[[x, y], x]$ and $[[x, y], y]$ are both the identity element). It suffices to show that $\phi$ is an isomorphism.

To show $\phi$ is surjective, note that for $a, b, c \in \mathbb{Z}$, $(a, b, c) = \phi([x, y]^c y^b x^a)$ in $H$.

To show $\phi$ is injective, we first claim that any element of $H'$ can be written in the form $[x, y]^c y^b x^a$ for some $a, b, c \in \mathbb{Z}$. The proof of this claim is left as an exercise for the reader (hint: use induction on the number of terms of $x$, $y$, $x^{-1}$, or $y^{-1}$ making up the expansion of a preimage in the free group $\langle x, y \rangle$, along with the identities $xy = [x,y] \cdot yx$, $x y^{-1} = [x,y]^{-1} \cdot y^{-1} x$, $x^{-1} y = [x,y]^{-1} \cdot y x^{-1}$, $x^{-1} y^{-1} = [x,y] \cdot y^{-1} x^{-1}$ in $H'$, and the fact that $[x,y]$ is in the center of $H'$). But then, $\phi([x,y]^c y^b x^a) = (a, b, c) = (0, 0, 0)$ trivially implies $[x,y]^c y^b x^a = 1$.

(Another valid approach would be to define $\psi : H \to H'$, $(a, b, c) \mapsto [x,y]^c y^b x^a$, and show $\psi$ is the inverse of $\phi$. In this approach, the hardest step would likely be showing that $\psi$ is actually a homomorphism -- for which it would be useful to prove the identity $x^a y^b = [x,y]^{ab} y^b x^a \in H'$ for $a, b \in \mathbb{Z}$.)

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.